Perchloric Acid Enhances Sensitivity and Reproducibility of the Ferric-Xylenol Orange Peroxide Assay - Gay, C.A.; Gebicki, J.M.
The ferrous oxidation in xylenol orange (FOX)assay for hydroperoxides suffers from very narrow pH optimum in the range 1.7-1.8. Most published protocols recommend 25 mM sulfuric acid as the solvent, but this in practice does not ensure the maintenance of correct pH in the presence of materials such as samples of biological origin. Substitution of perchloric for the sulfuric acid resulted in a lowering of the optimum pH of the assay to 1.1, a decreased dependence of the absorbance of the ferric-xylenol orange complex on acid concentration and decreased sensitivity to added compounds. Molar absorption coefficients of hydrogen peroxide, cumene, and butyl hydroperoxides and of hydroperoxide groups generated in oxidized protein and lipids were determined and found to be higher than in sulfuric acid. The optimum concentration of perchloric acid proved to be 110 mM. The new assay was designated as PCA-FOX, to distinguish it from the FOX methods based on sulfuric acid.
Keywords: HYDROPEROXIDE; LIPID PEROXIDE; PROTEIN PEROXIDE; XYLENOL ORANGE; PERCHLORIC ACID